The effects of drama-based activities as a language learning tool on learners’ motivation in Non-Malay-medium national schools in Malaysia - Man, Chang Fui; Sharif, Sabariah; May, Andrea Lee Jen; Talin, Rosy; Singh, Soon Singh Bikar (Indonesian Journal of Applied Linguistics, 2021)
Transitioning from Non-Malay-medium national primary schools to Malay-medium or English-medium secondary schools proved to be a struggle for many students due to the lack of emphasis on audio-lingual skills of the second language (L2) throughout their six-years of primary education. This study aims to explore the effects of drama-based activities as a language learning strategy on L2 learning motivation among students aged between 12 to 13 years old from Non-Malay-Medium National Schools. Six students were recruited through purposive sampling to participate in this qualitative experimental research. Over a period of 14 weeks, pre-intervention interviews (on the first week), intervention (over the span of 2 hours per week for 12 weeks), and post-intervention interviews (on the fourteenth week) were carried out. The content of the intervention was adapted from the Trinity College London’s Grade 4 Communication Skills syllabus. The instruments used for data collection include:(1) pre-determined pre-and post-intervention interview protocols and (2) classroom observation rubric. Two themes emerged in the analysis of this study: (a) language learning motivation and (b) affective filter. Findings revealed that participants were motivated and possessed self-confidence in the language learning process. The current study provides instructional implications for instructors and learners besides contributing to the novelty in the area of the research setting and sampling for future studies.